2008
DOI: 10.1021/es702449c
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic and Carcinogenic Hazards of Settled House Dust I: Polycyclic Aromatic Hydrocarbon Content and Excess Lifetime Cancer Risk from Preschool Exposure

Abstract: Settled house dust (SHD) may be a significant source of children's indoor exposure to hazardous substances including polycyclic aromatic hydrocarbons (PAHs). In this study, organic extracts of sieved vacuum cleaner dust from 51 homes were examined for the presence of 13 PAHs via GC/MS. PAHs were found in all samples with levels of total PAHs ranging between 1.5 and 325 µg g -1 . The PAH concentrations in the SHD were correlated with information contained in corresponding household questionnaires. Analyses show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
8
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 32 publications
9
89
8
7
Order By: Relevance
“…) (Lin et al, 2008;Chiang et al, 2009) and the Canadian maximum acceptable level of risk (1 × 10 -5 ) (Maertens et al, 2008). The current study indicates there is some concerns on adverse health impact related with PM 2.5 bounded PAHs exposure for preschool children via non-dietary exposure in home environment, based on the calculation of Eqs.…”
Section: Health Risk Assessmentmentioning
confidence: 63%
See 2 more Smart Citations
“…) (Lin et al, 2008;Chiang et al, 2009) and the Canadian maximum acceptable level of risk (1 × 10 -5 ) (Maertens et al, 2008). The current study indicates there is some concerns on adverse health impact related with PM 2.5 bounded PAHs exposure for preschool children via non-dietary exposure in home environment, based on the calculation of Eqs.…”
Section: Health Risk Assessmentmentioning
confidence: 63%
“…The cancer risks of WCs for ingestion rate of 50 and 100 mg day -1 were greatly higher than those of NNP for 851 and 567 times in that order. Although the cancer risks of NNP were much lower than those of WCs, its average values ranged from 10 -4 to 10 -3 (i.e., one cancer incidence case per million), which can be considered as unacceptable cancer risks (Maertens et al, 2008). These values are comparable to those of foundry workers (9.06 × 10 -4 and 1.09 × 10 -3 ) in Taiwan (Liu et al, 2010), but higher than those predicted as occupational exposure for sinter metal workers (3.18 × 10 -5 and 4.98 × 10 -5…”
Section: Health Risk Assessmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Investigators have reported that PAH dust concentrations were higher in urban compared with rural homes (Chuang et al, 1999;Maertens et al, 2004;Mannino and Orecchio, 2008), in smoking compared with non-smoking homes (Maertens et al, 2004;Mannino and Orecchio, 2008), in spring compared with summer (Murkerjee et al, 1997), and in homes with decreased cleaning frequency (Maertens et al, 2008). In the largest study of determinants of PAH in residential dust (N ¼ 583), investigators found that PAH concentrations were associated with residence age, the presence of gas heating (as opposed to electric heating), and estimated outdoor PAH air concentrations (Whitehead et al, 2011).…”
Section: Determinants Of Pah Levels In Residential Dustmentioning
confidence: 99%
“…Since people (especially kids, housewives and old people) spend approximately 85% of their lifetime indoors (Amorello et al, 2015;Rudel et al, 2003), indoor air quality has a prominent role in their health (Maertens et al, 2008). Moreover, healthy housing environment is one of the key indexes to evaluate social stability and development (Li et al, 2009;Tao et al, 2016); however, rapid industrialization and urbanization ha caused deterioration of human settlement environments in cities through increasing pollutant emissions (Kang et al, 2011;Whitehead et al, 2011;Xu and Shu, 2012).…”
Section: Introductionmentioning
confidence: 99%